Design of an automatic temperature and humidity measuring device in the oyster mushroom cultivation room - Permata, Riski Surya; Ilham, Dirja Nur; Risky, Muharratul Mina; Harahap, Muhammad Khoiruddin; Kurniadi, Sepri (LEMBAGA KAJIAN PEMBANGUNAN PERTANIAN DAN LINGKUNGAN (LKPPL), 2024)
Advances in science and technology have become the idea of a tool for the development of oyster mushroom cultivation which has increased following the large market demand. Cultivating oyster mushrooms in areas with high temperatures requires special care techniques. Current technological developments make it easier to maintain oyster mushroom cultivation, namely by automatically regulating the temperature and humidity in the cultivation room. With automatic temperature control, it can make maintenance easier and reduce failure in oyster mushroom production. To realize the simulation of automatic temperature and humidity control, several pieces of hardware are needed, namely temperature and humidity sensors, DC fan, LCD, power supply, and Arduino Uno as the processor. which are then combined into a system. The growth of oyster mushrooms is greatly influenced by the surrounding environmental conditions. Therefore, we must know the conditions that are suitable for growth before we cultivate oyster mushrooms. Usually, the growth of oyster mushrooms will be optimal throughout the year if the cultivation location is by its natural habitat, namely in a mountainous area with an altitude of between 400 - 800 meters above sea level and an air temperature of around 21 - 29 oC with a humidity level of around 60 - 80%. In general, farmers cultivate natural mushrooms in a room to obtain environmental conditions suitable for growth. Because mushrooms are very sensitive to temperature and humidity, it is necessary to monitor the temperature and humidity in the growing room.